Influencers as socio-technical actors: mapping the paths of influence and the traces of the digital influencers’ system in Italy - Locatelli, Elisabetta (Journal of Sociocybernetics, 2020)
In recent years, digital influencers or digital opinion leaders have emerged as a global phenomenon, one providing a rich field of investigation for several disciplines from sociology to marketing. The goal of the paper is to study this phenomenon by adopting an ecological approach, not focusing only on a single dimension but observing the influencer system as an environment with its own rules and subjects, examining the other components of the system and tracing the relationships between them. The original contribution of this paper is to conceptualize influencers as socio-technical actors, i.e. as social subjects that operate within technological platforms, and to adopt an interdisciplinary approach, starting from sociological and marketing studies on the influencer phenomenon and then moving on to STS studies that have focused on the social shaping of technology to shed light on how the influencers are transforming the (social) media system in which they are inserted and then the chain of communication industry. The argument will therefore start by reviewing the theories that address this phenomenon and by sketching a genealogy, tracing its roots in the cultural and social context of the participatory web and web 2.0. It will move, then, to investigate the dynamics of shaping social media platforms, reviewing the studies that have investigated them, from the Social Shaping of Technology approach to platform studies. The paper will apply the analysis to the Italian context, unfolding the dynamics of influence with the support of the case study of ClioMakeUp (the leading beauty creator in Italy), examples, and grey literature from the Italian context. In the final part, the paper will map the traces of the influencer system in Italy and the communication chain, focusing on the processes of mutual shaping between brands, communication agencies, influencer enterprises, regulatory bodies, media, and of course platforms. The STS approach proved to be useful in disentangling the several actors of the system, but as platforms evolved the opportunities for mutual shaping have gradually diminished as the balance of power seems to be tending in favor of the platforms. More research is needed to further understand the concepts of closure, script, and relevant social groups within social media platforms.